2015
DOI: 10.1097/mlr.0000000000000419
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the First 30 Days After Patients are Discharged to the Community From Hip Fracture Postacute Care

Abstract: Background Post-acute care (PAC) rehabilitation aims to maximize independence and facilitate a safe community transition. Yet little is known about PAC patients’ success in staying home post-discharge or differences on this outcome across PAC providers. Objectives Examine the percentage of PAC patients who remain in the community at least 30 days after discharge (i.e., successful community discharge) following hip fracture rehabilitation and describe differences among PAC facilities based on this outcome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 26 publications
1
45
0
Order By: Relevance
“…Our results are consistent with previous findings that older age predicts higher risk of unsuccessful community discharge among patients receiving postacute rehabilitation (Leland et al. ). This study also revealed a gender disparity: Men were less likely to experience a successful community discharge.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with previous findings that older age predicts higher risk of unsuccessful community discharge among patients receiving postacute rehabilitation (Leland et al. ). This study also revealed a gender disparity: Men were less likely to experience a successful community discharge.…”
Section: Discussionsupporting
confidence: 93%
“…Identifying PAC facility and regional‐level covariates (Leland et al. ; Reistetter et al. ), which might also account for differences in postacute outcomes, is also needed to inform future risk adjustment and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This renders rehabilitation providers ill-equipped to methodically enhance patient outcomes or engage in systematic quality improvement initiatives. With rehabilitation being an integral part of a patient's recovery process and PAC being the driver of raising healthcare costs, there is a need to classify what comprises high-quality care and its association to outcomes to enable rehabilitation to thrive in the healthcare reform framework (Leland et al, 2015; MaCurdy et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, patients experiencing a hip fracture have an increased risk of mortality, morbidity, hospital readmissions due to failed community transitions, and long-term institutionalization (Klop et al, 2016; Leland et al, 2015; Haleem et al, 2008; Parker et al, 2006; Berry et al, 2008; Haentjiens et al, 2003; Lyles et al, 2008; van Helden et al, 2007). Furthermore, this patient population has a high risk of additional falls and fractures, which often result in subsequent hospital readmissions, institutionalization, and functional decline (Ryg et al, 2009; Huntjens et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation